Clinical associations of serum interleukin-17 in systemic lupus erythematosus - Vincent, Fabien B (BioMed Central, 2013)
INTRODUCTION: Serum interleukin (IL)-17 concentrations have been reported to be increased in systemic lupus erythematosus (SLE), but associations with clinical characteristics are not well understood. We characterized clinical associations of serum IL-17 in SLE. METHODS: We quantified IL-17 in serum samples from 98 SLE patients studied cross-sectionally, and in 246 samples from 75 of these patients followed longitudinally over two years. Disease activity was recorded using the SLE Disease Activity Index (SLEDAI)-2k. Serum IL-6, migration inhibitory factor (MIF), and B cell activating factor of the tumour necrosis factor family (BAFF) were also measured in these samples. RESULTS: Serum IL-17 levels were significantly higher in SLE patients compared to healthy donors (P <0.0001). No correlation was observed between serum IL-17 and SLEDAI-2k, at baseline or during longitudinal follow-up. However, we observed that SLEDAI-2k was positively correlated with IL-17/IL-6 ratio. Serum IL-17 was significantly increased in SLE patients with central nervous system (CNS) disease (P = 0.0298). A strong correlation was observed between serum IL-17 and IL-6 (r = 0.62, P <0.0001), and this relationship was observed regardless of disease activity and persisted when integrating cytokine levels over the period observed (r = 0.66, P <0.0001). A strong correlation of serum IL-17 was also observed with serum BAFF (r = 0.64, P <0.0001), and MIF (r = 0.36, P = 0.0016). CONCLUSIONS: Serum IL-17 concentration correlates poorly with SLE disease activity but is significantly elevated in patients with CNS disease. IL-17/IL-6 ratio may be more useful than IL-17 or IL-6 alone to characterize Th17-driven disease, such as SLE. The association of other cytokines with serum IL-17 suggests that IL-17 may drive activation of diverse immune pathways in SLE.